2017
DOI: 10.1002/glia.23195
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative interaction of hepatocyte growth factor and neuregulin regulates Schwann cell migration and proliferation through Grb2-associated binder-2 in peripheral nerve repair

Abstract: The sequential reactive changes in Schwann cell phenotypes in transected peripheral nerves, including dedifferentiation, proliferation and migration, are essential for nerve repair. Even though the injury-induced migratory and proliferative behaviors of Schwann cells resemble epithelial and mesenchymal transition (EMT) in tumors, the molecular mechanisms underlying this phenotypic change of Schwann cells are still unclear. Here we show that the reactive Schwann cells exhibit migratory features dependent on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…Firstly, as revealed in B7-2KO mice, CXCL13 may be involved in the pro-inflammatory condition associated with local immune activation within neuropathic nerves. Secondly, even though HGF, TNF-α and CCLs may represent the local inflammatory condition in nerves, these cytokines could be induced as a result of the activation of innate immunity during WD 6,26,27 ; hence, they cannot specifically represent the pro-inflammatory condition in nerves. Finally, we found no significant increase in CXCL13 serum levels in patients with AMAN, an axonal form of GBS.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, as revealed in B7-2KO mice, CXCL13 may be involved in the pro-inflammatory condition associated with local immune activation within neuropathic nerves. Secondly, even though HGF, TNF-α and CCLs may represent the local inflammatory condition in nerves, these cytokines could be induced as a result of the activation of innate immunity during WD 6,26,27 ; hence, they cannot specifically represent the pro-inflammatory condition in nerves. Finally, we found no significant increase in CXCL13 serum levels in patients with AMAN, an axonal form of GBS.…”
Section: Discussionmentioning
confidence: 99%
“…Primary SC culture from neonatal rat sciatic nerves was performed as previously reported . For biochemistry and collection of conditioned medium, cells were used at 2–4 generations.…”
Section: Methodsmentioning
confidence: 99%
“…Alexa Fluor 488 or Cy3‐conjugated antibodies were used for the secondary antibodies. Immunofluorescence staining and western blot analysis were performed as previously described . The sources of antibodies and reagents will be provided upon request.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of PNS, HGF can enhance survival and axon outgrowth of cultured motor neurons 16 – 19 , and it is also known to interact with NGF to exert neurotrophic effects on sensory neurons 20 . Recently, it has been reported that Gab2 protein is required for the migration and proliferation of SCs and HGF could induce the activation of Gab2 to show such cellular effects 21 . However, whether c-met receptor has any role in peripheral nerve injury is largely unknown.…”
Section: Introductionmentioning
confidence: 99%